2009
DOI: 10.1017/s0144686x08007903
|View full text |Cite
|
Sign up to set email alerts
|

The health and relationship dynamics of late-life couples: a systematic review of the literature

Abstract: 455Late-life husband and wife relationships are increasingly recognised as an important factor in promoting wellbeing, particularly in terms of the health, social, emotional, financial and practical needs of older people. Knowledge of marital dynamics and how they affect both members of a couple remains scarce. This systematic review aimed to identify and appraise research that has focused explicitly on the dynamics of the relationship, as evinced by data from both spouses. Implementing rigorous identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
92
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 61 publications
2
92
0
5
Order By: Relevance
“…This was echoed by Hagedoorn et al (2011), whose review concluded that further studies are needed "to increase our knowledge of dyadic processes in cancer adaptation". This is of direct clinical relevance given the impact of dyadic processes on patients' and caregivers' physical and mental health (Meyler et al, 2007;Walker & Luszcz, 2009). Indeed, the efficacy of psychosocial interventions for cancer caregivers may be influenced by the patient-caregiver relationship (Waldron et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This was echoed by Hagedoorn et al (2011), whose review concluded that further studies are needed "to increase our knowledge of dyadic processes in cancer adaptation". This is of direct clinical relevance given the impact of dyadic processes on patients' and caregivers' physical and mental health (Meyler et al, 2007;Walker & Luszcz, 2009). Indeed, the efficacy of psychosocial interventions for cancer caregivers may be influenced by the patient-caregiver relationship (Waldron et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Spouses then may become mutual carers to maintain their independency as a couple (Rose & Bruce, 1995). More recently, studies go beyond this patient-caregiver perspective and start to focus on the dynamics of the marital relationship in late life (Walker & Luszcz, 2009). In their review, Walker and Luszcz (2009) specifically selected studies with dyadic data of older couples.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies go beyond this patient-caregiver perspective and start to focus on the dynamics of the marital relationship in late life (Walker & Luszcz, 2009). In their review, Walker and Luszcz (2009) specifically selected studies with dyadic data of older couples. Based on nine studies, these researchers concluded that older couples seemed to be rather resilient against the negative impact of illness in maintaining high levels of marital quality.…”
Section: Introductionmentioning
confidence: 99%
“…Spouses' health statuses are associated, as regards depressive and other psychological symptoms (7,8), cardiovascular risk factors (7,9) and health behaviours (7); in different age groups and cultural settings (7). Health concordance between spouses can be caused by similarities existing before marriage (7) or social influence during marriage (10).…”
Section: Introductionmentioning
confidence: 99%